PERENCANAAN EMBUNG JEMAWAN KABUPATEN KLATEN JAWA TENGAH - Fero Adi Putra; Ika Noviana Prasetyo; Sriyana Sriyana; Al Falah (Jurnal Karya Teknik Sipil, 2014)
Irrigation water demand and raw water in Klaten regency is increasing in line with population growth. Raw water needs in Klaten regency, District Jatinom, especially Jemawan village have been obtained from well water and for irrigation use pattern of rainfed. For the Government in this case the Department of Water Resources Management (PSDA) seeks to develop new sources of raw water by building Jemawan Small Dam. As the rainy season water reservoir, water reservoir can also be efficiently used in the dry season. Aside from being a source of raw water for daily use and meets the needs of water for irrigation, small dam also be an alternative flood mitigation in downstream areas of the river. Based on the mainstay discharge analysis by the method of F.J Mock obtained the discharge mainstay 20% dry minimum of 19,3 liters/sec. For the body design of the small dam used the flood discharge hydrological data HSS Gamma I method with flood discharge plan 100 years return period amounted 105,550 m3/sec. Jemawan Small Dam reservoir volume is 170.783,58 m3. Small dam design life is 20 years, can meet the needs irrigation with an area of 200 Ha and raw water needs for 3.513 people. The planned small dam 9,60 m high, with a base elevation ponds +221,00 m, +230,60 m dam crest elevation, surveillance 1,5 m high, 5 m wide dam crest, upstream slope of 1:3, 1:2,25 downstream slope. In planning this Jemawan Small Dam used Ogee threshold type spillway width 30 m with a height of 1,5 m and a spillway crest elevation of +228,00 m, using an eject pond flat type III with a length of 10 m. This project implementation is scheduled for 48 weeks with a budget plan of Rp.12.603.159.500,00.